ANALISIS PENGARUH KINERJA KEUANGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN - Prayoga, Nisthi; Gusnardi, Gusnardi; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to analyze the effect of financial performance and disclosure of Corporate Social Responsibility (CSR) on the value of the mining sector companies. The research object is all mining sector companies, but based on the completeness of the data, only 12 companies were sampled with the observation period from 2016 to 2018. The data analysis used is multiple linear regression. The results of this study indicate that financial performance and CSR disclosure have a positive effect on the value of the mining sector companies either simultaneously or partially. This shows that financial performance and CSR disclosure can increase firm value. This means that the higher the financial performance and CSR disclosure the higher the value of the mining sector companies.Key Words: Financial Performance, Corporate Social Responsibility Disclosure, and Firm Value.